Prevalence of Vitamin-D- Associated-Gestational Diabetes-Mellitus among Mothers in Third Trimester - Saba Ijaz; Rabeea Sattar; Rubba Batool; Tayyaba Shafique; Rabia Khusheed; Kaveeta Bansi, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
OBJECTIVE: This study was aimed to evaluate the association-between-Vit D-deficiency-and risk-of developing GDM-during pregnancy at a tertiary care Hospital. BACKGROUND: In the United States, Gestational diabetes mellitus (GDM) results in complication of 7–14% of gravidities. Another common side effect of pregnancy is vitamin D deficiency. It is unknown, nevertheless, if taking vitamin D supplements can stop GDM. According to recent studies, vitamin D supplementation can improve glucose and insulin tolerance. There is conflicting evidence from observational studies about association between GDM and low serum 25(OH) D levels. METHODOLOGY: A-case-control-study-was carried out at the department-of-Obstetrics & Gynecology, -Jinnah-Hospital, -Lahore from 01-07-2022 to 31-12-2022. Using consecutive sampling method. 122 pregnant females were inducted in the study. All the females aged between 20 to 40 years and parity less than five who presented with gestational age of more than 24 weeks by dating scan were made part of the study. The SPSS version 21 program was used to enter and analyze the data. To test for significance, post-stratification adjusted OR was calculated, with OR>1 being considered significant. RESULTS: In this study, out of 122 cases (61 in each group), 78.68% (n=48) in cases and 77.05 %( n=47) in controls were aged between 20-30 years, whereas 21.32 %( n=13) in cases and 22.95 %( n=14) in controls were aged between 31-40. Vitamin D deficiency in cases was 29.51 %( n=18) in cases and in controls 9.84 %( n=6) whereas. The odds ratio was 3.90 and p value was 0.007. CONCLUSION: This study reached to the conclusion that the risk of gestational diabetes mellitus is greatly increased by vitamin-D- during the third trimester of pregnancy.